Delays in Blood Work and Disease Burden: A Cross-Sectional Analysis of Unmet Blood Work Need and Seven Key Health Conditions Across 21 Countries - Eunice Chung; Louisa Ewald; Nicholas J. Kassembaum; Nicholas J. Kassembaum; Taylor Noyes; Emmanuela Gakidou; Emmanuela Gakidou; Ali H. Mokdad; Ali H. Mokdad (International Journal of Public Health)
ObjectivesThis study analyzes survey data across 21 countries to explore correlations between delays in blood testing and the prevalence of seven health conditions: thalassaemias, sickle cell disorders, malaria, HIV, high fasting plasma glucose, impaired kidney function, and high LDL cholesterol.MethodsWe analyzed Pandemic Recovery Survey data via multivariable logistic regression to compare blood test delays between individuals with and without medical conditions, while adjusting for sociodemographic factors. We also examined the disease burden using disability-adjusted life years (DALYs) and summary exposure values (SEV) rates.ResultsOur findings indicate profound disparities, with over 60% of respondents in Egypt, Nigeria, and India reporting they have never undergone blood tests. Individuals with existing medical conditions are significantly more likely to experience delays in blood work.ConclusionThere is a pronounced gap in blood work accessibility, particularly in countries with high disease burdens. Findings suggest an urgent need for interventions to improve routine blood test access for high-risk populations to reduce the underdiagnosis of significant medical conditions. Prioritizing timely and accessible blood testing can serve as a step towards mitigating healthcare disparities.